Roman Law and the Development of Private Law in Russia in the Modern Era - Gábor Hamza (Journal on European History of Law)
The document delves into the integration of Roman law principles into the Russian legal framework, particularly focusing on private law during the modern era. It explores the historical context, the transition, and the significant influence these legal norms had on shaping and evolving private law in Russia, highlighting the process of legal codification and adaptation within the Russian legal system.